EFL STUDENT’S DIFFICULTIES IN EXTENSIVE LISTENING ACTIVITIES: A THEMATIC CONTENT ANALYSIS - Indra Cipta Putra Mandiri; Muhammad Handi Gunawan; Suharno Suharno (University of Kuningan, 2022)
The study of extensive listening (EL) is a comparatively new field in comparison to its peer, extensive reading (ER). Extensive listening itself can be defined as an engaging and enjoyable listening activity that is beneficial in increasing one’s listening comprehension. Although there have been extensive studies in regards to the field of listening in general, the field of extensive listening receives relatively little attention. This study aims to uncover the difficulties encountered by EFL students in their extensive listening activities, and to contribute itself to the present gap of studies concerning extensive listening, specifically difficulties encountered in it. This study involves twenty-three EFL students under the class of listening for General Communication 1, and conducts a thematic analysis on the participants’ questionnaire and interview responses. The findings showed that the difficulties encountered by the participants in their extensive listening activities can be divided into three major categories, namely comprehension difficulties, technical difficulties, and motivational difficulties.